Systematic Literature Review: Assessment of Patients with Critical Illness and Nursing Outcomes - Praphasorn, Wannapa; Munyeun, Suparada (Princess of Naradhiwas University Journal, 2023)
The systematic literature review is aimed to summarize the know-how of assessment of patients with critical illness and nursing outcomes. According to the research reports during 2011-2021 by using guidelines for systematic literature review of Joanna Briggs Institute (2016) and result of systematic retrieval, it was found that there were totally 8 research papers which passed the selection criteria, including 1 experimental research, 2 quasi-experimental researches, 4 observational researches, and 1 descriptive research. The research tools were the form of assessment of research quality and the form of data extraction. The Researcher used the content analysis and summary. According to the result of systematic literature review and assessment of modified early warning sign, it was found that with the scoring result of 1-2 points, there was the highest survival chance of 85.5%. According to the assessment of quick sepsis organ failure, it was found that with the scoring result of 2 points or above, the death rate within and outside CCU could be predicted. According to the use of the form of scoring assessment of APACHE II and APACHE III, it was found that the death rate of patients was lower than the death rate under the criteria of APACHE II at the same scoring level, with statistical significance (p < 0.001) and according to the result of use of the form of assessment of patients with critical illness under the nursing concept of FANCAS in nursing students, it was found that nursing students had the knowledge and abilities to use the form of assessment of patients with critical illness, created from FANCAS patterns, at the intermediate level (X = 3.38, S.D. = .741). This systematic literature review will be useful for medial personnel’s application in assessment of patients for better nursing outcomes.